2018
DOI: 10.1371/journal.pone.0198791
|View full text |Cite
|
Sign up to set email alerts
|

Brain basis of cognitive resilience: Prefrontal cortex predicts better reading comprehension in relation to decoding

Abstract: ObjectiveThe ultimate goal of reading is to understand written text. To accomplish this, children must first master decoding, the ability to translate printed words into sounds. Although decoding and reading comprehension are highly interdependent, some children struggle to decode but comprehend well, whereas others with good decoding skills fail to comprehend. The neural basis underlying individual differences in this discrepancy between decoding and comprehension abilities is virtually unknown.MethodsWe inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 77 publications
0
21
0
1
Order By: Relevance
“…A separate line of research has investigated the role of EF in individuals with reading comprehension that is discrepantly higher than word decoding skills. For example, a recent study found that the left dorsolateral prefrontal cortex, an area that subserves EF, was associated with increased discrepancy between reading comprehension and decoding above and beyond covariates in children 10-16 years old (Patael et al, 2018). These results suggest that EFand corresponding brain regionsmay boost reading comprehension above and beyond decoding at this age.…”
Section: Executive Function and Reading Comprehensionmentioning
confidence: 95%
“…A separate line of research has investigated the role of EF in individuals with reading comprehension that is discrepantly higher than word decoding skills. For example, a recent study found that the left dorsolateral prefrontal cortex, an area that subserves EF, was associated with increased discrepancy between reading comprehension and decoding above and beyond covariates in children 10-16 years old (Patael et al, 2018). These results suggest that EFand corresponding brain regionsmay boost reading comprehension above and beyond decoding at this age.…”
Section: Executive Function and Reading Comprehensionmentioning
confidence: 95%
“…However, despite the fact that sleep disorders and sleep loss induce both sleepiness and cognitive deficits, it is not possible to directly assume that decremented cognitive performances are due to sleepiness. Indeed, sleep loss and sleep disorder may affect brain maturation, cognitive functions, and related brain mechanisms through many different processes (e.g., disruption of sleep related restorative brain processes, oxidative stress, and hypoxia in prefrontal cortex and other brain regions) [ 2 , 42 , 94 , 95 ]. Thus, it is possible to stress that, in order to support the idea that there is a relationship between sleepiness and cognition, there is a need of studies that assess directly and specifically the association between sleepiness and cognitive skills [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In order to establish a compensatory role for these systems, however, it is important to demonstrate their engagement in relation to behavioral performance (Hancock et al, 2017). The few studies that have done this have demonstrated both positive and negative associations between bilateral inferior frontal regions and reading-related skills (Bach et al, 2010;Horowitz-Kraus et al, 2013;Ingvar et al, 2002;Patael et al, 2018;Rumsey et al, 1994;Ryherd et al, 2018). We found that individuals with worse Word Attack scores in the Dys group recruited the bilateral inferior frontal regions to a greater extent.…”
Section: Decoding Correlatesmentioning
confidence: 67%